Cyto-adherence of Mycoplasma mycoides subsp. mycoides to bovine lung epithelial cells - Aye, R.; Mwirigi, M.K.; Frey, J.; Pilo, P.; Jores, Joerg; Naessens, Jan (Springer, 2015)
Background: Mycoplasma mycoides subsp. mycoides (Mmm) is the causative agent of contagious bovine pleuropneumonia (CBPP), a respiratory disease of cattle, whereas the closely related Mycoplasma mycoides subsp. capri (Mmc) is a goat pathogen. Cyto-adherence is a crucial step in host colonization by mycoplasmas and subsequent pathogenesis. The aim of this study was to investigate the interactions between Mmm and mammalian host cells by establishing a cyto-adherence flow cytometric assay and comparing tissue and species specificity of Mmm and Mmc strains. Results: There were little significant differences in the adherence patterns of eight different Mmm strains to adult bovine lung epithelial cells. However, there was statistically significant variation in binding to different host cells types. Highest binding was observed with lung epithelial cells, intermediate binding with endothelial cells and very low binding with fibroblasts, suggesting the presence of effective adherence of Mmm on cells lining the airways of the lung, which is the target organ for this pathogen, possibly by high expression of a specific receptor. However, binding to bovine fetal lung epithelial cells was comparably low; suggesting that the lack of severe pulmonary disease seen in many infected young calves can be explained by reduced expression of a specific receptor. Conclusions: Mmm bound with high efficiency to adult bovine lung cells and less efficiently to calves or goat lung cells. The data show that cyto-adherence of Mmm is species- and tissue- specific confirming its role in colonization of the target host and subsequent infection and development of CBPP.